2013
DOI: 10.4161/mabs.22854
|View full text |Cite
|
Sign up to set email alerts
|

Implications of receptor-mediated endocytosis and intracellular trafficking dynamics in the development of antibody drug conjugates

Abstract: The use of antibody-drug conjugates (ADCs) as a therapeutic platform to treat cancer has recently gained substantial momentum. This therapeutic modality has the potential to increase the efficacy and reduce the systemic toxicity associated with current therapeutic regimens. The efficacy of ADCs, however, relies on the proper exploitation of intracellular sorting dynamics of the antigen as well as the specificity, selectivity and pharmacokinetic properties of the antibody itself. Our understanding of endocytosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
172
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(172 citation statements)
references
References 67 publications
0
172
0
Order By: Relevance
“…In breast cancers expressing high levels of HER2, experience with T-DM1 has shown that tumor-selective expression of an ADC target and its ability to deliver DM1 to lysosomes are of paramount importance (43). However, despite its ability to effectively kill breast cancer cells expressing high levels of HER2, T-DM1 does not efficiently kill cells expressing low and intermediate levels of HER2, possibly because a relatively small amount of cell surface HER2 reaches lysosomes (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancers expressing high levels of HER2, experience with T-DM1 has shown that tumor-selective expression of an ADC target and its ability to deliver DM1 to lysosomes are of paramount importance (43). However, despite its ability to effectively kill breast cancer cells expressing high levels of HER2, T-DM1 does not efficiently kill cells expressing low and intermediate levels of HER2, possibly because a relatively small amount of cell surface HER2 reaches lysosomes (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…While conceptually simple, the effectiveness of an antibody-drug conjugate depends on the effectiveness of the antibody, drug, and the linker fastening the drug to the antibody. After systemic administration, the antibodydrug conjugate binds the targeted epitope on the surface of the cancer cell which then internalizes the antibody-drug conjugate by receptor mediated endocytosis (147). Once internalized, the cytotoxic drug is released from the antibody through either hydrolysis, enzymatic cleavage, of degradation of the antibody depending on the linker used.…”
Section: Antibody-drug Conjugatesmentioning
confidence: 99%
“…Given that some of the pathways regulated by Endo II are being considered in targeted therapies, the relative levels of Endo II expression in these patient samples may be relevant to the response to therapy. It is also worth noting that in the rapidly emerging field of antibody-drug conjugates for cancer therapy, biomarkers related to the endocytic pathways may be useful to predict response, since receptor internalization is a necessary step for release of these anticancer drugs (57).…”
Section: Discussionmentioning
confidence: 99%